Diferrocenes Bridged by a Geminal Diethynylethene Scaffold with Varying Pendant Substituents: Electronic Interactions in Cross-Conjugated System - Fan, Yang; Li, Hua-Min; Zou, Guo-Dong; Zhang, Xu; Pan, Ying-Le; Cao, Ke-Ke; Zhang, Meng-Li; Ma, Pei-Lin; Lu, Hai-Ting (Organometallics, 2017)
A series of geminal diethynylethene (gem-DEE) bridged diferrocenyl compounds with varying pendant substituents at the side chain, including xanthene, thioxanthene, dibenzo[a,d]cycloheptene, and fluorene, is reported with the aim of exploring electronic interactions in the cross-conjugated system. The compounds 9-[bis(ferrocenylethynyl)methylene]-9H-xanthene (1), 9-[bis(ferrocenylethynyl)methylene]-9H-thioxanthene (2), 5-[bis(ferrocenylethynyl)methylene]-5H-dibenzo[a,d]-cycloheptene (3), and 9-[bis(ferrocenylethynyl)methylene]-9H-fluorene (4) were synthesized and characterized by using spectroscopic methods and single-crystal X-ray diffraction analyses. Electrochemical measurements using the weakly coordinating electrolyte Na[B{C6H3(3,5-CF3)(2)}(4)] reveal the moderate electronic coupling between the ferrocenyl (Fc) termini. Hush analysis of the intervalence charge-transfer (IVCT) bands for the monocation species is suggestive of the weakly coupled Robin-Day class II mixed-valence compounds. DFT and TDDFT calculations suggest that the low-energy transitions of these compounds mainly involve a metal to ligand charge transfer (MLCT) transition from the iron center of ferrocenyl termini to the pendant substituent.